Peran Senyawa Bioaktif Dan Pendekatan Komputasi Dalam Desain Obat Modern: Tinjauan Kimia Medisinal - Amin, Saeful; Dhata, Khayra Revaline Aulya; Firdaus, Renno Zikrya; Ramdani, Muhammad Nabil (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
The advancement of modern medicinal chemistry is marked by a paradigm shift from conventional experimental approaches toward data-driven integration combining bioactive compound exploration and advanced computational technologies. This transformation is driven by the high cost, time consumption, and failure rates in the drug discovery process, necessitating more efficient and predictive strategies. This study aims to systematically and comprehensively examine the role of bioactive compounds and computational approaches in modern drug design, while also identifying the contributions, strengths, and limitations of each approach. The method employed is a descriptive-qualitative literature review of 15 relevant reputable scientific journals, analyzed through selection, thematic classification, and data synthesis based on structure–activity relationships and computational methodologies.The findings indicate that bioactive compounds derived from natural sources, such as flavonoids, alkaloids, and terpenoids, play a strategic role as lead compounds due to their structural diversity and broad pharmacological activities, despite challenges related to bioavailability and stability. Computational approaches, including molecular docking, quantitative structure–activity relationship (QSAR), and artificial intelligence (AI), have proven to enhance efficiency and accuracy in the identification, prediction, and optimization of drug candidates through molecular interaction simulations and data-driven predictive modeling. Furthermore, the integration of in silico and in vitro approaches serves as a critical framework for validating biological activity and reducing the risk of failure in later development stages.Overall, these findings highlight that no single method is sufficient on its own; instead, an integrated multidisciplinary approach is required to achieve more rational, selective, and sustainable drug design. Therefore, the synergy between bioactive compound exploration and data-driven computational technologies constitutes a fundamental foundation for the future development of innovative and efficient medicinal chemistry.